Pengaruh Flipped Classroom Menggunakan Google Classroom Berbahan Ajar Video Tutorial pada Mata Kuliah Kalkulus - Kinzie Feliciano Pinontoan; Mario Walean (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2020)
This study applied flipped classroom (FC) in Calculus lectures to investigate its effect to students’ learning achievement and motivation. Google Classroom (GC) was used for out-class sessions and tutorial videos were used to deliver the materials. An experiment was conducted toward a sample of 42 students of Universitas Prisma on Pharmacy, Architecture, and Technical Geology Department, which was consisted of two groups; (1) experiment group with the treatment of this study and (2) control group with conventional lectures. The instruments were written test as post-test to measure the learning achievement and questionnaire to measure the motivation score. Statistics test of 2-sample t and paired t were used in this study. The results showed that there was a positive effect of flipped classroom using Goggle classroom (FC-GC) with tutorial videos toward students’ learning achievement and their motivation in calculus lectures.